Viral delivery of C9orf72 hexanucleotide repeat expansions in mice leads to repeat-length-dependent neuropathology and behavioural deficits - Saul Herranz-Martin; Jayanth Chandran; Katherine Lewis; Padraig Mulcahy; Adrian Higginbottom; Callum Walker; Isabel Martinez-Pena y Valenzuela; Ross A. Jones; Ian Coldicott; Tommaso Iannitti; Mohammed Akaaboune; Sherif F. El-Khamisy; et al. (Disease Models & Mechanisms, 2017)
Intronic GGGGCC repeat expansions in C9orf72 are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Two major pathologies stemming from the hexanucleotide RNA expansions (HREs) have been identified in postmortem tissue: intracellular RNA foci and repeat-associated non-ATG dependent (RAN) dipeptides, although it is unclear how these and other hallmarks of disease contribute to the pathophysiology of neuronal injury. Here, we describe two novel lines of mice that overexpress either 10 pure or 102 interrupted GGGGCC repeats mediated by adeno-associated virus (AAV) and recapitulate the relevant human pathology and disease-related behavioural phenotypes. Similar levels of intracellular RNA foci developed in both lines of mice, but only mice expressing 102 repeats generated C9orf72 RAN pathology, neuromuscular junction (NMJ) abnormalities, dispersal of the hippocampal CA1, enhanced apoptosis, and deficits in gait and cognition. Neither line of mice, however, showed extensive TAR DNA-binding protein 43 (TDP-43) pathology or neurodegeneration. Our data suggest that RNA foci pathology is not a good predictor of C9orf72 RAN dipeptide formation, and that RAN dipeptides and NMJ dysfunction are drivers of C9orf72 disease pathogenesis. These AAV-mediated models of C9orf72-associated ALS/FTD will be useful tools for studying disease pathophysiology and developing new therapeutic approaches.